2015
DOI: 10.7314/apjcp.2015.16.17.7875
|View full text |Cite
|
Sign up to set email alerts
|

Relation of BAALC and ERG Gene Expression with Overall Survival in Acute Myeloid Leukemia Cases

Abstract: Background: The objectives of this study were to evaluate the expression of brain and acute leukemia, cytoplasmic (BAALC) gene and erythroblast transformation-specific related gene (ERG) in de novo cases of acute myeloid leukemia (AML) and identify roles in disease progression and outcome. Materials and Methods: This study included 50 newly diagnosed AML patients, along with 10 apparently healthy normal controls. BAALC and ERG expression was detected in the bone marrow of both patients and controls using real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
4
3
0
2
Order By: Relevance
“…Typically, BAALC mRNA isn't detected in normal individuals; there was a statistically significant difference in expression between patients group and control, similar to what was reported by other studies. [2,9] We found no correlation between age and BAALC gene expression, that agreed with what reported in other studies by Bienz et al, [10] and Metzeler et al [4] That differs from what was stated by Rashed et al, [11] who detected a significant correlation between high BAALC gene expression and age. Patients older than 45 years had higher High BAALC expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Typically, BAALC mRNA isn't detected in normal individuals; there was a statistically significant difference in expression between patients group and control, similar to what was reported by other studies. [2,9] We found no correlation between age and BAALC gene expression, that agreed with what reported in other studies by Bienz et al, [10] and Metzeler et al [4] That differs from what was stated by Rashed et al, [11] who detected a significant correlation between high BAALC gene expression and age. Patients older than 45 years had higher High BAALC expression.…”
Section: Discussionsupporting
confidence: 90%
“…BAALC gene expression no significant association different between sex, similar to what was declared in other studies. [7,11,12] Patients in normal cytogenetic risk group had higher BAALC overexpression than the other two groups; this concurs with Zhou et al [13] We found that patients with CN-AML had higher (TLC, LDH level and blast cell count) and lower (PLT count and Hb level) that were statistically significant compared to the other groups. In patients with CN-AML median BAALC was 3.21, that was a statistically significant difference than the other two groups.…”
Section: Discussionsupporting
confidence: 88%
“…32 However, some studies found no significant difference in CD34+ between high and low expression groups of BAALC. 29 There was also no significant difference between CD34 + and CD34in terms of WT-1 expression in Anderson et al study 4 that was similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…15 In a study of 50 AML patients, CR was different between low and high expression of ERG. 29 Moreover, in a meta-analysis of seven studies, it was showed that high ERG expression was associated with lower CR and higher relapse in cytogenetically normal AML patients. 14 ERG was involved in cell differentiation, proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bu genlerin ifade eksiliği çeşitli hematolojik malignitelerin ve solid tümörlerin ortaya çıkmasına neden olmaktadır. Miyeloid ve lenfoid hücre serili lösemi gelişimine neden olması, hfematopoezde görevli olan hücrelerin çoğalma kapasitelerini artırmasını düzenlemesi ile olmaktadır (12). ERG 21. kromozomun uzun kolu üzerine konumlanmıştır ve 12 ekzondan oluşmaktadır (13).…”
Section: Pedi̇atri̇k öNcü B-all De Aday Bi̇yo-beli̇rteç Genlerunclassified